The seven faces of philanthropy a new approach to cultivating major donors - Prince, Russ Alan; File, Karen Maru (Jossey-Bass, 1994)
Seven Faces of Philanthropy introduces to you the Seven Faces approach-a powerful tool that enables development professionals to maximize their effectiveness when approaching major donors for gifts. The authors identify and profile seven types of major donors and offer you detailed strategies on how to approach them. Both novice and expert fundraisers will find this framework a valuable supplement to existing strategies and techniques.